THE USEFULNESS OF FORMATIVE ASSESSMENTIN WORKING WITH ADOLESCENTS AT RISK OF SOCIAL MALADJUSTMENT. INDICATIONS AND LIMITATIONS - Aleksandra Tłuściak-Deliowska; Katarzyna Choszczyk-Kwiatkowska (Probacja, 2025)
The article aims to demonstrate the relevance and usefulness of implementing formative assessment strategies in everyday work with adolescents at risk of social maladjustment. The article presents: (1) the profile of a pupil at risk of social maladjustment; (2) their special educational needs based on this profile; (3) the principles of formative assessment as an appropriate concept for working with such pupils; and (4) possible limitations and challenges. The conclusion reached was that formative assessment is a promising practice and a particularly appropriate method of supporting the development of pupils at risk of social maladjustment, helping them acquire agency in their learning process. However, there is a shortage of research on the role of formative assessment in work with adolescents at risk of or already experiencing social maladjustment.